INCREASED VOLUME OF DOCUMENTS CIRCULATION AS A FACTOR OF DECLINE OF UNIVERSITY’S ECONOMIC EFFICIENCY - Dmitry A. Endovitskiy; Yuriy A. Bubnov; Karina M. Gaidar (Высшее образование в России)
The main issue of the article isan unprecedented analysis of constantly increasing volume of documents circulation, mainly external, at higher education institution. On the basis of accurate data, it is emphasized that it leads to the decline of economic efficiency and decreased quality of educational institution functioning. Furthermore, changing qualitative and quantitative characteristics produce negative economic, organizational, and psychological consequences in the activities of the university. The authors come to a conclusion that in order to solve the problem stated above the optimization of documents circulation is necessary and beneficial for higher education institution functioning.